Pencinta Alam Sebagai Bentuk Peran Pemuda Di Tengah Tantangan Kehidupan Kota - Jalu Lintang Yogiswara Anuraga (Universitas Gadjah Mada, 2016)
The important role of youth as an agent of change in the society is questioned. Seeing the modern society that has new challenge which is the capitalist society culture impacts in alienation. The capitalist culture that occurs in urban society is considered as a change that gives impact at youth role and it becomes the dominant culture. Seeing this phenomena, this article will answer how youth do the counter culture toward the dominant culture. This dominant culture is seen as a culture that can alienate the youth from their surrounding and this will weaken the youth role in society. Counter culture is defined as a culture that can counter the dominant culture in the society. While alienantion is defined as someone’s clutter from certain thing that alienates him or her from himself or herself, others, or the surrounding where she or he lives like in fromm concept. This article will present the life pattern of nature lovers. This article will begin by describing the life of nature lovers from how it is formed, the daily life of nature lovers and their value or view as a form counter culture toward the dominant culture which is the capitalist culture that alienates youth from their environment. This article is written based on descriptive analysis of interview, observation, and literature review in nature lovers organisation in university level which is often called Mapala.